The Effect of Hot Conceptual Change on Students’ Views on the Nature of Science - Savas, Emre; Kocakulah, Aysel (Science Insights Education Frontiers, 2025)
This study aims to investigate the effect of the teaching model developed for hot conceptual change on middle school 7th-grade students’ understanding of the Nature of Science (NOS) aspects. In this qualitative and exploratory study, activities were carried out with 24 students of two classes in a village school in the South Marmara region using a pretest-posttest control group quasi-experimental design. Students in control (inquiry-based learning-IBL) and experimental (hot conceptual change based on IBL) groups used instructions for teaching the NOS topics in the 7th-grade light unit. The pre-test and post-test data on the NOS were obtained by the Opinions on the Nature of Science Questionnaire (ONSQ). In the analysis of ONSQ data, students’ views on the aspects of the NOS were scored according to the adequate (3), variable (2), and weak (1) categories. These scores were converted into gain scores and considered in the comparison between the groups regarding those aspects. Semi-structured interviews were conducted with two students from each group before and after the implementation. The gains related to NOS aspects obtained with the instructions carried out for seven weeks were presented and results were discussed in the context of the literature on hot conceptual change, IBL, and NOS. Finally, suggestions were made for new research and teaching practices for teachers.